Application of Prophetic Democratic Leadership Mudirah at Pondok Pesantren Tahfiz Putri Khoiro Ummah Yogyakarta - Nizma Armila; Abdus Salam DZ; Dian Widiantari (Action Research Journal Indonesia (ARJI), 2024)
In Indonesia, pesantrens are traditionally led by men (kiai/Ustāż), but female leadership (nyai/Ustāżah) is increasing, though often perceived as less participatory due to the dominance of male authority. Women's leadership in pesantrens plays a crucial role in shaping santriwati (female students), yet research on its impact on student achievement is limited. This study analyzes the leadership role of the Mudīrah in developing the achievements of santriwati at Pondok Pesantren Tahfiẓ Putri Khoiro Ummah Yogyakarta. Using a qualitative approach and phenomenological methods, data were gathered from key figures such as the Mudīrah, teachers, caregivers, and students. Data collection involved observation, interviews, and document analysis, with validity ensured through credibility and triangulation tests. Pondok Pesantren Tahfiẓ Putri Khoiro Ummah, established in 2010, focuses on Qur'ān memorization and Islamic character development. Ustāżah Hj. Umi Hajar, Lc, who co-founded the pesantren, now leads it as Mudīrah. Her leadership style combines democratic and prophetic traits—valuing subordinates’ potential, involving them in decision-making, and embodying Islamic values such as siddiq, amānah, tabligh, and faṭānah. She creates a positive and innovative environment that fosters both academic and non-academic achievements, particularly in Qur'ān memorization. Her role as a caregiver, mentor, and manager supports the overall development of the santriwati, helping them meet pesantren standards.